Plasma thyroid hormones concentrations in donkey stallions (Equus caballus) - BUGALIA, N. S; SHARMA, SATISH; GARG, S L; KUMAR, VIRENDER; CHANDER, SURESH (The Indian Journal of Animal Sciences, 2013)
Thyroid function was studied in normal libido (reaction time 30 min, n=6) at 15 days interval during breeding (july and August) and nonbreeding seasons (December and January). Sighificantly (P